Exploring Grammatical Errors Among Foreign Language Learners: A Study of Islamic Educational Management Students (Class B) at STIT Palapa Nusantara - Ozi Satria (Formad English Foundation NTB Jakarta, 2026)
Grammar plays an essential role in helping learners produce clear and meaningful communication in English. However, many foreign language learners still experience difficulties in applying grammatical rules accurately, especially in writing. This study aims to explore the types of grammatical errors made by foreign language learners and to identify the most common errors found in their written texts. The study employed a descriptive qualitative research design using an error analysis approach. The participants of the study were students learning English as a foreign language who were asked to complete a writing task on a given topic. The students’ written texts were collected as the primary data and analyzed using the error analysis procedures proposed by Stephen Pit Corder and further discussed by Rod Ellis. The results of the analysis revealed several types of grammatical errors, including verb tense errors, subject–verb agreement errors, article errors, preposition errors, pronoun errors, and sentence structure errors. Among these categories, verb tense and subject–verb agreement errors were the most frequently occurring errors in the students’ writing. The findings indicate that learners still face considerable challenges in mastering English grammar, particularly in applying grammatical rules consistently in written communication. These results suggest that English language teaching should provide more focused grammar instruction, contextualized learning activities, and continuous feedback to help learners improve their grammatical accuracy. Overall, this study contributes to a better understanding of grammatical difficulties experienced by foreign language learners and provides insights that may help teachers develop more effective strategies for teaching English grammar.